Penyuluhan Hukum “Meningkatkan Kesadaran Pemahaman Hukum Lingkungan Kepada Masyarakat (Dalam Rangka Memperingati Hari Cinta Puspa dan Satwa)" - Eza Aulia; Phoenna Ath Thariq; Rachmatika Lestari; Rahmad Jhoanda (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
The phenomenon of right of ownership disputes is a big problem that exists in the civil society of Nagan Raya Regency. Especially in the Rawa Tripa area at Suka Makmur District, another problem is related to the lack of community understanding of peat area protection and land clearing methods which are carried out using burning patterns. Based on observations also found a number of cases of land disputes between civil society and corporations in the Rawa Tripa area. The implementation of this community service is in the form of legal counseling which is carried out face-to-face by delivering material related to the theme of community service. The results and benefits obtained from the implementation of this legal counseling are able to provide understanding and legal awareness to the community related to rights of ownership, duties and functions of the civil society in preserving the environment, as well as education related to the constitutional rights of citizens in the environment and natural resources sector.